A Study of Reading Literacy Factors and Differences between Native and Immigrant Students Based on 2018 PISA Database - Fang-Chung Chang (National Taipei University of Education, 2022)
The purpose of this study was to analyze the differences between native, first-generation and second-generation immigrant children´s family socioeconomic status, expectation to attend university, segregation index and reading literacy, and the impact of these factors on reading literacy. Based on the data of 74 countries in the 2018 PISA, the conclusions were followings: 1) The socioeconomic status and reading literacy of native-born families were significantly higher than those of second- and first-generation immigrant children. The expectation for local students to go to university was not significantly higher than that of immigrant children, and the rate of speaking other languages at home was significantly lower than that of immigrant children. 2) The reading scores of the second-generation immigrant were significantly higher than those of the first-generation, while the ratio of speaking other languages at home was significantly lower than that of the first-generation students. 3) The socioeconomic status of native, immigrant children had an effect on improving reading literacy. Different generations immigrant children´s desire to attend university contributed to improved reading literacy. 4) The rate of non-instructional language used at home by immigrant children had no significant effect on literacy; the segregation index of immigrant children had a negative significantly effect on literacy. The contribution of this research lies in finding that the family background, language usage at home, social isolation, and education-expectations of immigrant children were important factors for improving reading literacy. We should pay attention to the social isolation of immigrant children, and schools should pay attention to the language use of immigrant children at home to avoid a decline in reading literacy. Specific recommendations were provided.